SOSIALISASI HASIL HUTAN BUKAN KAYU (HHBK) SEBAGAI SOLUSI MASALAH KEHUTANAN DAN EKONOMI MASYARAKAT - Tan, Lieke; Siruru, Herman; Titarsole, Jimmy; Liliefna, Leonard Dantje; Maail, Rohny Setiawan; Fransz, Jimmy Johanson; Parera, Lydia Riekie; Mustamu, Poppy (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
Non-Timber Forest Products are a potential that can be managed to overcome forestry and community economic problems. Improvement of eucalyptus oil processing and management can affect the income of eucalyptus oil farmers. The purpose of this community service activity is to provide knowledge about improving the quality of eucalyptus oil through improving eucalyptus oil processing methods and utilizing eucalyptus leaf waste as an energy source through making charcoal briquettes. The stages of the activity are: 1) The initial approach is carried out with the head of the Buru FMU to facilitate meetings with the KPH-assisted farmer groups to be addressed, 2) Implementation of counseling, lectures and questions and answers about various knowledge related to the utilization of Non-Timber Forest Products. How is eucalyptus oil processed and how is the management carried out by eucalyptus oil farmers, and 3) Observation of eucalyptus oil cooking places to see the raw materials and boilers used. This activity was carried out cooperatively and well because the Waspait village community was very enthusiastic about their curiosity which was reflected when participating in the counseling which was carried out by building dialogue in the form of questions related to the eucalyptus oil processing activities carried out.